The Effect of Using Podcast on Listening Achievement of the Eighth Grade Students of Junior High School - Dewayani, Viandra Yashinta; Tasnim, Zakiyah; Hudori, Rizki Febri Andika (English Education Study Program, 2023)
This study was conducted to identify the effect of using Podcast on listening achievement of the eighth grade students of Junior High School. Based on the preliminary study, it was known that the eighth grade students in one of the junior high school in Situbondo had never used Podcast as a medium of learning listening skill and the teacher often used audio from the internet to teach listening skill. This study applied quantitative method using quasi-experimental with post-test only design. The two classes at that school were chosen as participants for this research, one class belonged to experimental group and the other belong to control group. The students in experimental group were taught listening skill by using Podcast as a medium of learning, while the students belonged to control group were taught by listening to the teacher read the text. The data were analyzed by using Independent Sample t-test formula in SPSS. The results indicated that there was a significant effect of using Podcast on listening achievement of the eight grade students. It was proven that the significant value (2-tailed) was 0.001 and it was lower than 0.05.